2014
DOI: 10.1021/bi5002757
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Direct Involvement of the Substrate TCP Radical in Functional Switching from Oxyferrous O2 Carrier to Ferric Peroxidase in the Dual-Function Hemoglobin/Dehaloperoxidase from Amphitrite ornata

Abstract: The coelomic O2-binding hemoglobin dehaloperoxidase (DHP) from the sea worm Amphitrite ornata is a dual-function heme protein that also possesses a peroxidase activity. Two different starting oxidation states are required for reversible O2 binding (ferrous) and peroxidase (ferric) activity, bringing into question how DHP manages the two functions. In our previous study, the copresence of substrate 2,4,6-trichlorophenol (TCP) and H2O2 was found to be essential for the conversion of oxy-DHP to enzymatically acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Alternatively, it has also been proposed that substrate radicals, themselves formed from trace amounts of the ferric enzyme reacting with substrate and hydrogen peroxide, oxidize oxyferrous DHP to the catalytically-active ferric form. 59,60 Here, the slow reactivity of Compounds ES/II with pyrrole, leading to the pyrrole radical cation, would also be consistent with the substrate radical activation of oxyferrous DHP in a manner that would lead to the observed differential reactivity when compared to the ferric enzyme.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Alternatively, it has also been proposed that substrate radicals, themselves formed from trace amounts of the ferric enzyme reacting with substrate and hydrogen peroxide, oxidize oxyferrous DHP to the catalytically-active ferric form. 59,60 Here, the slow reactivity of Compounds ES/II with pyrrole, leading to the pyrrole radical cation, would also be consistent with the substrate radical activation of oxyferrous DHP in a manner that would lead to the observed differential reactivity when compared to the ferric enzyme.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have shown that oxyferrous DHP can only be activated by H 2 O 2 in the presence of substrate (TCP, 59,60 5-bromophenol, 38 or 4-nitrophenol 39 ), leading to Compound II formation, whereas its activation in the absence of a substrate leads to the bleaching of the Soret band and/or slow conversion to Compound RH without the formation of any observable fast timescale reactive intermediates. 58 Here, we investigated the reactivity of preformed DHP Compound II with pyrrole using sequential double-mixing stopped-flow methods: oxyferrous DHP B containing 1 equivalent TCP was reacted with 10 molar equivalents of H 2 O 2 at pH 6, incubated in an aging line for 83 s to allow for the maximum accumulation of Compound II [419 (Soret), 545, 585 (sh) nm, black], 58 and subsequently mixed with an additional 50 equiv of pyrrole (Figure S11C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the amino acid sequence defines the unique three‐dimensional structure of a protein, conversion of the function of a protein without modifying its amino acid sequence is limited. An example of a native bifunctional heme protein is dehaloperoxidase, which has been shown to convert with its substrate radical from an O 2 ‐binding hemoglobin to a peroxidase …”
Section: Introductionmentioning
confidence: 99%
“…An example of a native bifunctional heme protein is dehaloperoxidase, which has been shown to convert with its substrate radical from an O 2 -binding hemoglobin to a peroxidase. 18,19 Proteins in the cytochrome c (cyt c) protein family have been studied extensively in terms of protein folding and stability. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Met80 and His18 are coordinated to the heme iron in cyt c, creating a relatively high redox potential for electron transfer.…”
Section: Introductionmentioning
confidence: 99%